On the hydrological Effect of Forests in the zone of insufficient Precipitation - Raev, I. (Macedonian Journal of Ecology and Environment, 1994)
Traced is the historical evolution of tree vegetation, trends in the changes of the ecological conditions of Europe, as well as the consequences of the establishment of coniferous stands in the zone with insufficient precipitation. Cited are quantitative data on the hydrological effect of coniferous and broadleaved species, proving the hypothesis of the superiority of broadleaved vegetation in hydrological aspect, in comparison with coniferous vegetation: lower interception more net precipitation, more quantities of water for transpiration and higher vitality of stands.